Importance of socio-economic and institutional factors in the collection of dry forest products: The case of gum and resin in Jawi District, Northwest Ethiopia - Sheko, M.; Kassa, G.; Abebaw, D.; Kassa, H. (Elsevier, 2023)
Although the important role of dry forests in livelihoods is immense, empirical evidence on the role of socioeconomic factors in the collection of dry forest products is still lacking. This study aimed to assess the determinants of household participation in dry forest product collection and its contribution to the household economy in Jawi district. The primary data were collected from 259 randomly selected households. The determinant factors affecting household participation in dry forest product (gum and resin) collection and the level of revenue from gum and resin were evaluated using a Heckman 2-stage selection model. According to the findings of this survey, dry forest revenue accounts for 23.69% of the total annual household income. Our findings reveal that age, proximity to the forest, distance to the market, participatory forest management (PFM) membership, frequency of forest extension, and poor wealth status have a substantial impact on a household's engagement in dry forest product collection and the level of income generated from engagement in dry forest product collection. Policies and strategies aimed at improving the well-being of households in the country's dry forest areas should focus on the market development of resources to boost the income of local people.